Assessment of Acute Serum Iron, Non-Transferrin-Bound Iron, and Gastrointestinal Symptoms with 3-Week Consumption of Iron-Enriched Aspergillus oryzae Compared with Ferrous Sulfate - Bries, Amanda E (Curr Dev Nutr, 2019)
BACKGROUND: Iron deficiency anemia (IDA) is a widespread nutritional deficiency, and iron supplementation, especially with ferrous sulfate (FeSO(4)), is the most common strategy to treat IDA; however, compliance is often poor with daily FeSO(4) owing to negative side effects. In a previous study, iron from iron-enriched Aspergillus oryzae [Ultimine(®) Koji Iron (ULT)] was absorbed similarly to FeSO(4). OBJECTIVES: The main objective of this study was to assess the safety of consuming ULT in terms of increasing non-transferrin-bound iron (NTBI) and gastrointestinal distress. METHODS: Young female participants (n  = 16) with serum ferritin <40 μg/L were randomly assigned to a double-blind, 9-wk crossover study with a 3-wk placebo/washout period between treatments. Oral FeSO (4) and ULT supplements containing 65 mg Fe were administered daily for 21 consecutive days. On day 1, serum iron (SI), percentage transferrin saturation (%TS), and NTBI were measured for 8 h on the first day of iron consumption. Changes in biochemical indicators were evaluated after 3 wk consumption. Side effects questionnaires were completed weekly on 2 randomly selected weekdays and 1 weekend day for the entire study. RESULTS: SI, %TS, and NTBI were all markedly higher during hours 2–8 (P < 0.001) with FeSO(4) than with ULT. Oxidative stress, inflammatory, and kidney and liver function markers remained unchanged with both supplementations compared with placebo. Changes in iron status markers were not significantly different among the 3 treatments. Individual or global side effects were not significantly different among all treatments. Even when common side effects of nausea, constipation, and diarrhea were combined, FeSO(4) treatment had a significantly higher effect than ULT (P = 0.04) and placebo (P = 0.004) only at week 3, but the difference was not significant between ULT and placebo. CONCLUSIONS: Low NTBI production and fewer common gastrointestinal side effects with ULT suggest that it is a safe oral iron supplement to treat IDA. This trial was registered at clinicaltrials.gov as NCT04018300.